2021
DOI: 10.1136/bmjopen-2020-045794
|View full text |Cite
|
Sign up to set email alerts
|

Psychological impact of the COVID-19 pandemic within institutional quarantine and isolation centres and its sociodemographic correlates in Qatar: a cross-sectional study

Abstract: SettingThe State of Qatar has had one of the highest COVID-19 infection rates globally and has used state-managed quarantine and isolation centres to limit the spread of infection. Quarantine and isolation have been shown to negatively affect the mental health of individuals. Qatar has a unique population, with around 90% of the population being economic migrants and a majority being blue-collar workers and labourers.ObjectivesThis study was carried out to evaluate the psychological impact of institutional iso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
43
2
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(51 citation statements)
references
References 26 publications
4
43
2
2
Order By: Relevance
“…An important finding within this study was the centrality of participants' need for closeness and social interaction with loved ones as a motivator for deviation from the measures. This finding aligns with the results of studies investigating the impact of the COVID-19 pandemic on loneliness and social well-being (Reagu et al, 2021;Banerjee & Rai, 2020). In a study by Reagu et al (2021) participants reported the lack of contact with family members to be one of the main sources of their experienced distress.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…An important finding within this study was the centrality of participants' need for closeness and social interaction with loved ones as a motivator for deviation from the measures. This finding aligns with the results of studies investigating the impact of the COVID-19 pandemic on loneliness and social well-being (Reagu et al, 2021;Banerjee & Rai, 2020). In a study by Reagu et al (2021) participants reported the lack of contact with family members to be one of the main sources of their experienced distress.…”
Section: Discussionsupporting
confidence: 85%
“…This finding aligns with the results of studies investigating the impact of the COVID-19 pandemic on loneliness and social well-being (Reagu et al, 2021;Banerjee & Rai, 2020). In a study by Reagu et al (2021) participants reported the lack of contact with family members to be one of the main sources of their experienced distress. Indeed, in the context of physical distancing measures, the basic human need for closeness and belonging can be chronically frustrated in the name of collective health and safety (Hagerty et al, 1992;McLeod, 2007, Ristau, 2011.…”
Section: Discussionsupporting
confidence: 85%
“…30 Based on our previous study, the majority of our participants were migrant workers, and participants with COVID-19 had higher depressive (PHQ-9 score 6.1 v. 2.8; P < 0.001) and anxiety scores (GAD-7 score 4.8 v. 2.3; P < 0.001) compared with controls. 15 In addition, our participants comprised quarantined individuals. Social isolation and loneliness in the context of quarantine can lead to symptoms of depression, anxiety and post-traumatic stress disorders.…”
Section: Discussionmentioning
confidence: 99%
“…A study conducted in United Arab Emirates (UAE) in the initial phase of the COVID-19 pandemic (April 2020) found that positive religious coping was associated with lower depression scores in Muslims but not Christians (Thomas and Barbato, 2020). Two studies from Qatar, one conducted in elderly population being quarantined for COVID-19, also supported a negative association between religiosity and depression-anxiety (Ouanes et al, 2021;Reagu et al, 2021). These ndings suggest that health care professionals should assess spirituality as it may be another facet to help build resilience at times of stress.…”
Section: Discussionmentioning
confidence: 99%